Student perceptions of two simulated learning environments in paediatric audiology. - Wilson, W. J.; Schmulian, D.; Sher, A.; Morris, S.; Hill, A. E. (International Journal of Audiology, 2020)
Objective: To determine audiology student perceptions of two simulated learning environments (SLE) in paediatric audiology. Design: A one-shot case study design. Study sample: Fifteen audiology students who completed questionnaires after participating in two SLEs, one simulating auditory brainstem response (ABR) assessments of neonates in a hospital ward and one simulating visually reinforced orientation audiometry (VROA) assessments of young children in an audiology clinic. Results: The students responded positively to 11/11 areas of audiometric testing and client interaction in both SLEs, to 7/7 aspects of their interactions with the mannequins in both SLEs, and to 8/8 aspects of their interactions with fellow students playing the role of parent in the ABR SLE and 7/8 of these aspects in the VROA SLE. The students reported low levels of anxiety towards both SLEs but rated the ABR SLE more highly than the VROA SLE in areas of preparedness, effectiveness, realism, pre-SLE training, reinforcement of lecture content, and overall usefulness. Conclusions: The participating students responded positively to almost all aspects of both SLEs. Further research is warranted using research designs capable of determining if these SLEs directly improve student abilities as they transition from academic settings to clinical placements in paediatric audiology.